Biogranules applied in environmental engineering - Milferstedt, Kim; Hamelin, Jerome; Park, Chul; Jung, Jinyoung; Hwang, Yuhoon; Cho, Si-Kyung; Jung, Kyung-Won; Kim, Dong-Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The efficiency of wastewater treatment with renewable energy generation has been greatly improved with the development of biogranules. In this review article, various types of biogranules (methanogenic, hydrogenic, aerobic, anaerobic ammonium oxidation, and oxygenic photogranules) applied in environmental engineering are introduced along with their history, theories on how they are formed, physico-chemical and morphological characteristics, and the effects on enhanced performance. Although each individual granule has its own characteristics, there might be something in common that the formation is related with high production of extracellular polymeric substances, and they all have high hydrophobicity, settling velocity, and density. To our knowledge, this is the first review article dealing with various types of biogranules. The information given herein will provide a chance for a deep understanding on biogranules in both fundamental research and engineering point of views. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: SEQUENCING BATCH REACTOR; SLUDGE BLANKET REACTOR; FERMENTATIVE HYDROGEN-PRODUCTION; ANAEROBIC AMMONIUM OXIDATION; AEROBIC GRANULAR SLUDGE; WASTE-WATER TREATMENT; EXTRACELLULAR POLYMERIC SUBSTANCES; HYDRAULIC RETENTION TIME; UASB REACTOR; BIOHYDROGEN PRODUCTION